Settling assays testing the substrate preference of larvae of the cold-water coral Desmophyllum pertusum (syn. Lophelia pertusa) - Strömberg, Susanna M.; Rossi, Marion; Vonderscher, Paul; Larsson, Ann I. (Frontiers in Environmental Science, 2025)
The cold-water coral Desmophyllum pertusum form complex habitats for associated fauna at landscape scale, however, these habitats have been degraded by human activities over the last decades. In all European OSPAR regions the status is poor and declining, with increasing realization that active restoration measures are needed to restore some of the lost complexity. The prerequisite for successful larval recruitment is still unknown for this species. The aim of this study was to find the optimal material composition of artificial reef (AR) units for larval recruitment to guide a large-scale restoration effort in the Skagerrak, Sweden. We tested nine different substrates, including different blends of concrete, metallurgic slag, and ceramic materials in a settling assay with settling-competent larvae. Substrates containing Ground Granulated Blast Furnace Slag (GGBFS) and silica oxide produced, together with samples of 3D printed concrete, significantly higher values both considering time spent on substrate as well as attachment rate compared to concrete made of standard Portland cement (PC). We propose that this is due to the higher content of magnesium in the GGBFS compared to PC. Incorporation of GGBFS in the concrete can potentially increase longevity of the ARs and will lower the carbon footprint. With increased larval interest in concrete with GGBFS this is a triple win and increases the potential for a successful restoration effort.